THE INFLUENCE OF MOTIVATION AND PHYSICAL WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PT. ORGANIC FAIR PROSPEROUS SOUTH TANGERANG - Suwanto, Suwanto; Abdurohman , Dede; Ilham , Nurul (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
The purpose of this study is to determine the effect of Motivation and Physical Work Environment on Employee Performance at PT. Organik Adil Sejahtera, South Tangerang. The research method used is quantitative. The sampling technique employed a saturated sample, resulting in a sample of 62 respondents. Data analysis includes validity tests, reliability tests, classical assumPTion tests, regression analysis, correlation coefficients, determination coefficients, and hypothesis testing. The results show that Motivation has a significant effect on Employee Performance with a determination coefficient value of 20.2%, and hypothesis testing yielded t-count > t-table (3.902 > 1.671). The Physical Work Environment also has a significant effect on Employee Performance with a determination coefficient value of 71.3%, with hypothesis testing showing t-count > t-table (12.254 > 1.671). Motivation and Physical Work Environment simultaneously have a significant effect on Employee Performance with the regression equation Y = 2.928 + 0.070X1 + 0.981X2. The determination coefficient value is 71.8%, while the remaining 28.2% is influenced by other factors not studied, such as Work Discipline, Job Satisfaction, and Compensation. Hypothesis testing obtained an F-count > F-table value (75.039 > 3.150).